Glomerulonephritis with Crescents in Children: Etiology and Predictors of Renal Outcome - Alsaad, K. (International Scholarly Research Network, 2011)
Objective. To investigate the clinicopathological features and outcome of glomerulonephritis with crescents among Saudi children. Method. This is a retrospective study of cases of crescentic glomerulonephritis (CrGN) seen over a 9-year period. Histological features and renal function were recorded. Results. Thirty-seven cases were enrolled. The mean percent of glomeruli with crescents was 39% (±19). Lupus nephritis (LN) was the commonest etiology (54.1%). At presentation, the serum creatinine (SCr) was 218.2 (±174.3) umol/l, and 57.1% of the cases had nephrotic range proteinuria. By the end of the observation period, SCr dropped to 81.0 (±67.7) umol/l (P = 0.001). Worsening renal function was associated with younger age (P = 0.002), non-LN etiology (P = 0.01), more crescents (P = 0.019), and ATN (P = 0.05). At the end of the followup, more patients in the LN group were dialysis-free (P = 0.017) and had improved renal function (0.01) than in the non-LN group. Using multivariate analysis, the only independent factor found to predict need for dialysis or change in SCr level was percent of globally sclerosed glomeruli (P = 0.034). Conclusion. LN is the main cause of CrGN in our cohort of children. The LN group had less globally sclerorsed glomeruli and better renal prognosis than the non-LN group.